Development of Learning Tools Based on the TPACK Framework on Reaction Rate Material to optimize Student HOTS - Lendriadi, Lendriadi; Sutrisno, Sutrisno; Syamsurizal, Syamsurizal (Program Magister Teknologi Pendidikan Universitas Jambi, 2019)
This kind of research is development research. The subjects of research are 31 students of class XI IPA 2 SMAN 8 in Muaro Jambi. The instrument used a questionnaire responses of students, teachers' questionnaire responses, observation sheet of learning activity, HOTS assessment instruments, and TPACK integration instruments of teachers. The results are indicated on learning activities at the meeting I 96.15%, meeting II 96.68%, meeting III 97.22%, and meeting IV 97.22% , all of them belong to the category of